Analysis and comparison of dynamic behavior of heat exchangers for direct evaporation in ORC waste heat recovery applications from fluctuating sources. (15th April 2018) - Jiménez-Arreola, Manuel; Pili, Roberto; Wieland, Christoph; Romagnoli, Alessandro
Highlights: Dynamic behavior of two types of ORC evaporators for direct heat exchange is studied. The dependence of response time on geometric dimensions and materials is highlighted. Implications in pressure drops, volume and weight of heat exchangers are included. Fin and tube evaporators with large diameters are preferred for slow responses. Slow-response ORC evaporators can dampen source fluctuations in WHR applications. Abstract: Organic Rankine Cycle (ORC) is one of the most prominent technologies for power generation from waste heat sources. Due to their nature, as residual energy from an upstream process, waste heat sources typically present a fluctuating behavior that makes the recovery of the waste heat a challenging task. Direct evaporation from the waste heat carrier has gained substantial interest, especially on volume and weight sensitive applications where the introduction of an additional intermediary thermal oil heat exchanger can hinder the feasibility of the system. Because of the highly dynamic operation of direct evaporators under fluctuating waste heat sources, it is important to consider the thermal response time of the evaporator already at the design stage. In this paper, a systematic analysis and comparison of the dynamic response of two types of ORC evaporators for direct heat transfer between an exhaust gas and the organic working fluid is performed. Based on detailed dynamic models and simulations, maps are built to highlight in a generalized, compact and systematic way the dependence of the thermal response time of the evaporators on the geometric design and boundary conditions and its implications on the weight, volume and pressure drops. The analysis and application of the methodology to diesel engines long haul duty trucks, shows that fin and tube evaporators with large tube diameters and small cross-sectional areas of the exhaust side are the preferred option for high thermal inertia design, while louver fin multi-port flat tubes evaporators with large port diameters are better for fast response, despite the high pressure drops.